The influence of progressive muscle relaxation on stress, blood pressure, and quality of life in hypertension patients in the working area of Muliorejo Puskesmas, deli Serdang regency - Siregar, Abdul hanif; Gultom, Agustina boru (International Journal of Advanced Nursing Studies, 2018)
Hypertension is most commonly found in the primary care. It is very important to be warded off since it can cause the incidence of sickness and death. The management through lifestyle is very potential to control blood pressure and even to decrease the need for pharmacological management. The objective of this research was to analyze the influence of progressive muscle relaxation on stress, blood pressure, and quality of life in hypertension patients in the Working Area of Muliorejo Puskesmas, Deli Serdang Regency. The research used the quantitative method with quasi-experimental non-equivalents group control design. The samples were 30 respondents for both treatment and control groups, taken by using consecutive sampling technique. The data were analyzed by using dependent t-test and independent t-test. It could be concluded that there was the influence of progressive muscle relaxation on stress, blood pressure, and quality of life in hypertension patients. It is recommended that using progressive muscle relaxation be seriously considered as a nursing intervention as a complementary therapy for decreasing stress, stabilizing blood pressure, and improving quality of life in hypertension patients in the Working Area of Muliorejo Puskesmas, SunggalSubdistrict, DeliSerdang Regency.